Advances in the study of behavior - Naguib, Marc (Advances in the study of behavior, 2009)
Advances in the Study of Behavior was initiated over 40 years ago to serve the increasing number of scientists engaged in the study of animal behavior. That number is still expanding. This thematic volume, Vocal Communication in Birds and Mammals, makes another important "contribution to the development of the field" by presenting theoretical ideas and research to those studying animal behavior and to their colleagues in neighboring fields.